De Carter à Reagan : La politique salvadorienne des États-Unis - Toinet, Marie-France (Études internationales, 1982)
Ever since Monroe's doctrine and up to President Carter, the American foreign policy in Latin America has been remarkably continuous both from the point of view of objectives - the maintenance and extension of American influence and domination - and that of the pressures required to attain them - from direct military intervention to economic sanctions, including clandestine activities of destabilization. Carter came to power and from then on that policy rested on different principles which became expressed, particularly in the case of El Salvador, in pressures for the respect of human rights, a temporary suspension of aid from the Interamerican Development Bank and in the immediate recognition of the regime which followed the coup d'État of october 1979 and which made possible a third option between a reactionary dictatorship and a takeover by the Marxists. The principles were once again altered under President Reagan for whom the fight against communism and international terrorism is a priority.Latin America acquired a new strategic importance and El Salvador became the scene of the East-West conflict, the symbol of American determination to contain Soviet expansionism. But Reagan's policy in El Salvador had to be restrained confronted as it was by opposition both internal, from the public, and external through the stand taken by the Allies. In spite of starting doctrinal differences, Carter's and Reagan's policies in El Salvador are very similar, both showing incoherence and inefficiency. They are heirs to a situation and an intellectual tradition which they perpetuate, one clumsily, the other cheerfully. But the failure of the Reagan administration is even more patent than that of its predecessor. The United States have only one alternative left, military intervention or negotiations with the guerilla, and furthermore they risk "losing" El Salvador the Vietnam or the Nicaragua way.